Mixed-Potential Integral Equation Based Characteristic Mode Analysis of Microstrip Antennas. (15th November 2016) - Chen, Yikai; Guo, Liwen; Yang, Shiwen
Abstract : A characteristic mode (CM) formulation is developed for the modal analysis of microstrip antennas. It is derived from the mixed-potential integral equation (MPIE) with spatial-domain Green's functions for multilayered media, where spatial-domain Green's functions take into account the effect of the multilayered media. The resultant characteristic currents and fields are orthogonal with each other among different orders of modes. Together with the eigenvalues and their deduced indicators, the CMs provide deep physical insights into the radiation mechanisms of microstrip antennas. Numerical results are presented to confirm CM formulation's effectiveness and accuracy in determining the resonant frequencies, radiating mode currents, and modal fields of microstrip antennas. As opposed to the very popular CM formulation for conducting bodies, comparative studies are presented to show the quite different modal analysis results by considering the multilayered media.